The Effect of Emotional Exhaustion on Psychological Well-Being Among Employess with High Pressure - Hanifa Putri Wardhani; Erik Saut H Hutahaean; Ferdy Muzzamil (Inovan Publisher, 2026)
Emotional exhaustion is one of the most common psychological problems experienced by employees due to high job demands. This condition has the potential to reduce psychological well-being, which is essential for individuals to perform their work functions effectively. This study aimed to examine the effect of emotional exhaustion on psychological well-being among employees experiencing high levels of work pressure. A quantitative approach was employed involving 152 employees selected through purposive sampling. The research instruments consisted of the Emotional Exhaustion Scale and the Psychological Well-Being Scale. Data were analyzed using Spearman’s rho correlation and the Generalized Linear Model (Ordinal Logistic Regression). The results revealed a significant negative relationship between emotional exhaustion and psychological well-being (ρ = -0.630; p < 0.001). Furthermore, regression analysis indicated that emotional exhaustion significantly affected psychological well-being, contributing 39.7% of the variance. The findings suggest that higher levels of emotional exhaustion are associated with lower levels of psychological well-being among employees. These results highlight the importance of managing emotional exhaustion as an effort to enhance employees’ psychological well-being in high-pressure work environments.